Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,x.\left(x+7\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x+7=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=-7\end{cases}}}\)
\(2,\left(x+12\right).\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x+12=0\\x-3=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-12\\x=3\end{cases}}}\)
\(3,\left(-x+5\right).\left(3-x\right)=0\)
\(\Rightarrow\orbr{\begin{cases}-x+5=0\\3-x=0\end{cases}\Rightarrow\orbr{\begin{cases}-x=-5\\x=3\end{cases}\Rightarrow}\orbr{\begin{cases}x=5\\x=3\end{cases}}}\)
\(4,24:\left(3x-2\right)=-3\)
\(3x-2=-8\)
\(3x=-6\)
\(x=-2\)
\(5,-45:5\left(-3-2x\right)=3\)
\(5\left(-3-2x\right)=-15\)
\(-3-2x=-3\)
\(2x=0\)
\(x=0\)
\(6,x.\left(2+x\right)\left(7-x\right)=0\)
\(x=0\) hoặc \(\orbr{\begin{cases}2+x=0\\7-x=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-2\\x=7\end{cases}}}\)
\(7,\left(x-1\right)\left(x+2\right)\left(-x+3\right)=0\)
TH1: x-1=0 TH2 : x+2=0 TH3: -x+3=0
x=1 x=-2 -x=-3 => x=3
23 tháng 5 2016 lúc 8:41
a. /2x-1/=/x+2/
2x-1= x+2 hoặc 2x-1=-x-2
x=3 hoặc 3x=-1
x=3 hoặc x=-1/3
\(\left(\frac{x+1}{2}\right)\cdot\left(\frac{2}{3-2X}\right)=0\)
=> \(\orbr{\begin{cases}\frac{x+1}{2}=0\\\frac{2}{3-2x}=0\end{cases}}\)
(=)\(\orbr{\begin{cases}x+1=0\\3-2x=0\end{cases}}\)
(=)\(\orbr{\begin{cases}x=-1\\x=\frac{3}{2}\end{cases}}\)
Vậy x= - 1 hoặc x=\(\frac{3}{2}\)